2020
DOI: 10.1186/s12886-020-01506-w
|View full text |Cite
|
Sign up to set email alerts
|

Eiology and prognosis of canalicular laceration repair using canalicular anastomosis combined with bicanalicular stent intubation

Abstract: Background To evaluate the etiology of lacrimal canalicular laceration and explore the possible risk factors influencing prognosis. Methods The data of 142 patients (142 eyes) with lacrimal canalicular lacerations who were surgically treated using canalicular anastomosis combined with bicanalicular stent intubation between March 2017 and March 2018 were reviewed. The analyzed data contained demographic information, types of trauma, injury locations, associated additional ocular injuries, and surgical outcomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…These patients are also more often male than female, with studies suggesting a predominance of 2:1 to 4:1. [11][12][13] Blouse hooks are a notable cause of canalicular lacerations in breastfeeding infants. 14 Older patients often present with fall injuries.…”
Section: Canalicular Injuriesmentioning
confidence: 99%
See 3 more Smart Citations
“…These patients are also more often male than female, with studies suggesting a predominance of 2:1 to 4:1. [11][12][13] Blouse hooks are a notable cause of canalicular lacerations in breastfeeding infants. 14 Older patients often present with fall injuries.…”
Section: Canalicular Injuriesmentioning
confidence: 99%
“…Indirect injuries are also more commonly associated with extensive injuries elsewhere in the orbit. Although these etiologies vary significantly depending on geographic location and acute care setting, indirect injuries appear to be more common, 13,24,25 although one large retrospective review also found that direct injuries occur with comparable frequency. 26 When there is a suspicion for canalicular injury, it is important to identify any canalicular dehiscence precisely for repair (►Figs.…”
Section: Canalicular Injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 There is a risk of lacrimal drainage dysfunction with epiphora, if not appropriately managed with lacrimal canalicular anastomosis, combined with bicanalicular or monocanalicular stent intubation for primary canalicular laceration repairs. 7 …”
Section: Introductionmentioning
confidence: 99%